Horaz, Carm. II, 9–11: Eine Mitteltrias - Maurach, Gregor (Hyperboreus, 2018)
The three central odes of Horace, book 2 are interpreted in a new way. In contrast to current scholarship, it is shown that Carm. 2. 9–11 form a closely knit triad. If this holds true, it is no longer advisable to lay a compositional break after Carm. 2. 10. The composition of book 2 has to be reconsidered.